People, profiles, and purchases: Investigating the impact of environmental cues in social commerce - Morgan M. Bryant; Rituparna Basu (Cogent Business & Management, 2023)
Technology, digital advances, and social media are increasingly used to facilitate and influence online consumer purchasing behavior. Growth at the intersection of e-commerce, social networking usage, and functionality has given rise to the social commerce phenomenon. Social commerce sites allow consumers and sellers to engage in two concurrent types of interaction during the buying process. Consumers engage in marketing content from sellers and user-generated content from other consumers. This study investigates how social commerce sites' combined e-commerce and social networking functionality may impact consumer purchasing behavior. It focuses on seller-generated and user-generated social cues communicated through profile pictures, logos, and other social networking practices (e.g. "follows," "likes") and their correlation to retail shop performance indicators on a social commerce site. Using a sample of social and commercial performance indicators from retail shops on "Etsy.com" and a negative binomial regression analysis, we evaluate the effect of social signals on consumer purchasing behavior with a classical Stimulus-Response framework. Findings suggest consumers are more likely to purchase from shops with seller-generated social cues and show greater engagement in the volume of reviews and follows. More importantly, these features also appear to lower the negative impact of the age of an online shop. This finding may be advantageous to new entrants to social commerce or online retail outlets.
Keywords: 650; consumer behavior; negative binomial regression; seller-generated content; social commerce; stimulus-response model; user-generated content